A Safe‐by‐Design Strategy towards Safer Nanomaterials in Nanomedicines. Issue 45 (30th January 2019) - Yan, Liang; Zhao, Feng; Wang, Jing; Zu, Yan; Gu, Zhanjun; Zhao, Yuliang
Abstract: The marriage of nanotechnology and medicine offers new opportunities to fight against human diseases. Benefiting from their unique optical, thermal, magnetic, or redox properties, a wide range of nanomaterials have shown potential in applications such as diagnosis, drug delivery, or tissue repair and regeneration. Despite the considerable success achieved over the past decades, the newly emerging nanomedicines still suffer from an incomplete understanding of their safety risks, and of the relationships between their physicochemical characteristics and safety profiles. Herein, the most important categories of nanomaterials with clinical potential and their toxicological mechanisms are summarized, and then, based on this available information, an overview of the principles in developing safe‐by‐design nanomaterials for medical applications and of the recent progress in this field is provided. These principles may serve as a starting point to guide the development of more effective safe‐by‐design strategies and to help identify the major knowledge and skill gaps. Abstract : The most important categories of nanomaterials with clinical potential and their toxicological mechanisms are summarized. An overview of the principles in developing safe‐by‐design nanomaterials for medical applications together with the recent progress in this field is then provided.